Prioritizing Signaling Information Transmission in Next Generation Networks - Baraković, Jasmina; Bajrić, Himzo; Kos, Mladen; Baraković, Sabina; Husić, Amir (Journal of Computer Networks and Communications, 2011)
Next generation transport network is characterized by the use of in-band signaling, where Internet Protocol (IP) packets carrying signaling or media information are mixed in transmission. Since transport resources are limited, when any segment of access or core network is congested, IP packets carrying signaling information may be discarded. As a consequence, it may be impossible to implement reachability and quality of service (QoS). Since present approaches are insufficient to completely address this problem, a novel approach is proposed, which is based on prioritizing signaling information transmission. To proof the concept, a simulation study was performed using Network Simulator version 2 (ns-2) and independently developed Session Initiation Protocol (SIP) module. The obtained results were statistically processed using Statistical Package for the Social Sciences (SPSS) version 15.0. Summarizing our research results, several issues are identified for future work.